Vesico‐amniotic shunting for lower urinary tract obstruction in a fetus with VACTERL association. (September 2016) - Kanasugi, Tomonobu; Kikuchi, Akihiko; Haba, Gen; Sasaki, Yuri; Isurugi, Chizuko; Oyama, Rie; Sugiyama, Toru
Abstract: Newborn cases of VACTERL association with lower urinary tract obstruction (LUTO) are rare and there have been no reports on those patients undergoing fetal therapy in English literature. We successfully performed vesico‐amniotic shunting in a fetus having LUTO caused by abnormality of the external genitalia at 16 weeks' gestation. Although fetal karyotype was normal 46XY, follow‐up fetal ultrasound examinations revealed ventriculomegaly in the brain, a small stomach and a right multicystic dysplastic kidney. MRI at 31 weeks' gestation suggested lobar type holoprosencephaly. Diagnosis of VACTERL association was confirmed postnatally. We consider that vesico‐amniotic shunting is indicated for a fetus of VACTERL association with LUTO if the parents wish the procedure after genetic counseling and explanations about the fetal conditions.